2012
DOI: 10.1016/j.psychres.2012.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, compassion fatigue, and compassion satisfaction among staff in community-based mental health services

Abstract: Providing care to individuals with complex mental health needs can be stressful. However, little research has focused on the emotional, cognitive, and physical consequences of providing mental health care. The aim of this study is to assess burnout (BO), compassion fatigue (CF) and compassion satisfaction (CS) among staff at the four community-based mental health services (CMHS) of Verona, Italy. All staff were asked to complete anonymously the Professional Quality of Life Scale, the General Health Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 22 publications
5
114
0
2
Order By: Relevance
“…Such a reality has been linked to greater burn-out of staff, clinical judgment errors and dissatisfaction of both nurses and patients (Rossi et al, 2012). Furthermore, our results point to the possible relationship between the way a psychiatric nurse understands the etiology of mental illness and her own emotional condition.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Such a reality has been linked to greater burn-out of staff, clinical judgment errors and dissatisfaction of both nurses and patients (Rossi et al, 2012). Furthermore, our results point to the possible relationship between the way a psychiatric nurse understands the etiology of mental illness and her own emotional condition.…”
Section: Discussionmentioning
confidence: 65%
“…The exposure to patients' violence is frequently accompanied by feelings of uncertainty and inability to predict the patients' behavior (Partridge, Martin, Harari, & Dhesi, 2013). These stress-residues might contribute to job dissatisfaction and burn-out among nurses (Rossi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is unlikely, however, as prior research has found that burnout significantly increases and compassion for patients significantly decreases with greater time spent working in a psychiatric facility. [23] Further, it was not possible to collect direct patient outcomes for this study, though anecdotal evidence suggests that staff training in DBT skill coaching techniques resulted in fewer unit shutdown and seclusion and restraint procedures. Finally, the study was conducted specifically in a child and adolescent residential facility.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary traumatic stress symptoms are similar to those of posttraumatic stress disorder (PTSD) (Figley, 1995), whereas vicarious trauma primarily involves cognitive changes related to processing disturbing accounts of clients' traumatic experiences (Sabin-Farrell & Turpin, 2003). Compassion fatigue has been identified as a commonly occurring reaction in mental health professionals (Ray, Wong, White, & Heaslip, 2013;Rossi et al, 2012). Compassion fatigue has been identified as a commonly occurring reaction in mental health professionals (Ray, Wong, White, & Heaslip, 2013;Rossi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%